Prospective evaluation of radiocephalic arteriovenous fistula to determine the causes for non maturity with clinical and ultrasonography-doppler - Sameer Bhuwania; Rajesh Goel; Ravi Bansal; Sanjiv Saxena (Indian Journal of Vascular and Endovascular Surgery, 2021)
Introduction: The RC-AVF is the most important tool for hemodialysis considered to be the life line of patients. In our study, we have tried to find the incidence of AVF non maturation and the physical and ultrasonological parameter which can predict its non maturation. Materials and Methods: Radio-cephalic AVF surgery was done taking into account the inclusion and exclusion criteria with a follow up period of 6 weeks. The cases were evaluated pre-operatively and post-operatively using clinical and DUS. Results: 91 cases were studied with a success surgical outcome in 54.9% (50) of patients. The mean age of 46.04 yrs, male sex and less diabetes (46%) was associated with a matured RC-AVF surgical outcome. Mean preoperative artery diameter of > 0.21 ± 0.04 cm and vein diameter of > 0.20 ± 0.03 cm was seen in the matured cases. Incremental test and Resistive index was normal in 62% and 80% of the matured cases respectively, while calcification of feeding artery was associated with poor outcome. Further Clinical examination showed sensitivity 88% and specificity 95% whereas Doppler studies showed a sensitivity of 100% and specificity of 92.6% to successfully diagnose matured cases. Thrombosis (51%) was the most common cause of AVF failure followed by juxta anastomosis stenosis (14%). Conclusion: In this study we found that a thorough pre-operative evaluation of the vessels of RC-AVF can predict its maturation. Also a regular follow-up and use of clinical and imaging studies can help diagnose and timely salvage a failing AVF.